Enantioselective assembly of multi-layer 3D chirality. Issue 3 (16th December 2019) - Wu, Guanzhao; Liu, Yangxue; Yang, Zhen; Jiang, Tao; Katakam, Nandakumar; Rouh, Hossein; Ma, Liulei; Tang, Yao; Ahmed, Sultan; Rahman, Anis U; Huang, Hongen; Unruh, Daniel; et al.
Abstract: The first enantioselective assembly of sandwich-shaped organo molecules has been achieved by conducting dual asymmetric Suzuki-Miyaura couplings and nine other reactions. This work also presents the first fully C-C anchored multi-layer 3D chirality with optically pure enantiomers. As confirmed by X-ray diffraction analysis that this chiral framework is featured by a unique C2 -symmetry in which a nearly parallel fashion consisting of three layers: top, middle and bottom aromatic rings. Unlike the documented planar or axial chirality, the present chirality shows its top and bottom layers restrict each other from free rotation, i.e., this multi-layer 3D chirality would not exist if either top or bottom layer is removed. Nearly all multi-layered compounds showed strong luminescence of different colors under UV irradiation, and several randomly selected samples displayed aggregation-induced emission (AIE) properties. This work is believed to have broad impacts on chemical, medicinal and material sciences including optoelectronic materials in future.